Sedimentation under variable shear stress at lower reach of the Rupnarayan River, West Bengal, India. Issue 1 (1st April 2017) - Maity, Swapan Kumar; Maiti, Ramkrishna
Abstract: The lower reach of the Rupnarayan River has been deteriorated and incapacitated due to continuous sedimentation (26.57 million m 3 shoaling in last 25 years). Attempts have been made to explain the causes and mechanisms of sedimentation in connection to the seasonal fluctuation of shear stress. River depth and water velocity was measured by echo-sounder and current meter respectively. Textural analysis of grains was done by sieving technique. Available and critical shear stress (N/m 2 ) have been calculated following Du Boys (1879), Shield (1936) and Van Ledden (2003) formula. The lack of available energy to transport a particular grain size during low tide (in dry season) is the main reason behind the rapid sedimentation in this area. Most of the places (>75%) having negative deviation of shear stress (available shear stress lesser than critical shear stress), during low tide are characterized by deposition of sediments. The presence of mud (silt and clay) above the critical limit (15%) in some of the sediment samples generates the cohesive property, restricts sediments entrainment and invites sedimentation.